Separate Application of Vermicompost and Mycorrhization Enhances Antioxidant Production and SPF in Anadenanthera colubrina (Vell.) Brenan Seedlings - João Gabriel Lira de Carvalho; Eduarda Lins Falcão; Carmelo José Albanez Bastos Filho; Qiang-Sheng Wu; Fábio Sérgio Barbosa da Silva (Microbiology Research)
Arbuscular mycorrhizal fungi (AMF) and vermicompost can be efficient in enhancing the accumulation of metabolites, whereas there are no reports about their effects on antioxidant bioactive molecules and Sun Protection Factor (SPF) in Anadenanthera colubrina, a species used in cosmetic formulations. We hypothesized that the combination of AMF inoculation and vermicompost supplementation would synergistically optimize the production of these compounds and improve the antioxidant capacity and SPF of the plant leaves. A completely randomized experiment was set up in a factorial design with three mycorrhizal inoculation treatments (control, Acaulospora longula, and Gigaspora albida) and two substrate proportions (soil alone and soil with 10% vermicompost). After 126 days, the leaves were harvested to evaluate the content of primary metabolites, phenolics, antioxidant capacity, and SPF. Vermicompost did not synergize with AMF to enhance biomolecule synthesis in A. colubrina; instead, it neutralized the mycorrhizal effects. However, plants grown in soil supplemented with vermicompost showed an increase in metabolite and SPF accumulation compared to those grown solely in soil. Seedlings colonized by G. albida and grown in soil also exhibited enhanced anabolism. Therefore, this is the first report in the literature regarding the mitigating effect of vermicompost application on the SPF of mycorrhizal plants. Future studies should consider analyzing these factors in field conditions to attest the need of these agricultural tools.